1995
DOI: 10.1021/ma00112a008
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Measurements of the Nylon 6 Glass Transition Made Possible by the New Dynamic DSC

Abstract: Although it has long been known that the glass transition temperature (T,) of nylons changes significantly with moisture content, literature to date has lacked reliable measurements of this type, primarily due to the changes in moisture during the Tg scanning experiments. Introduction of the new dynamic DSC technique has allowed us to quantify the dependence of Tg on % relative humidity for nylon 6 and nylon 66. By eliminating the possibility of moisture pickup, we have been able to separate the effect of crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…If one disregards sample differences, e.g. molecular weight which was not given by Khanna et al [26], then their results imply that T g of 319.6 K for commercial nylon-6 at 1 atm [14] (Fig. 4) corresponds to a water content of ca.…”
Section: Glass Transition Behavior Of Nylon-6 and Mwcnt/nylon-6 Compomentioning
confidence: 88%
See 1 more Smart Citation
“…If one disregards sample differences, e.g. molecular weight which was not given by Khanna et al [26], then their results imply that T g of 319.6 K for commercial nylon-6 at 1 atm [14] (Fig. 4) corresponds to a water content of ca.…”
Section: Glass Transition Behavior Of Nylon-6 and Mwcnt/nylon-6 Compomentioning
confidence: 88%
“…It is well known that the moisture content significantly affects T g of nylon-6, which has been studied in detail by Khanna et al. [26]. If one disregards sample differences, e.g.…”
Section: Glass Transition Behavior Of Nylon-6 and Mwcnt/nylon-6 Compomentioning
confidence: 99%
“…Data such as those in Figure 4(c) show that the oriented segments relax at a higher temperature (T g $ 80-90 8C) than the unoriented segments (T g $ 30-50 8C). 62 The higher T g fraction is called the rigid amorphous fraction (RAF), [63][64][65] and the lower T g fraction corresponds to the conventional amorphous fraction. It is sometimes thought that the RAF is at the fold surface of the lamellae.…”
Section: Glass Transitionmentioning
confidence: 99%
“…Thus, for PA-6, Khanna et al found that: T g % 326-0.168w-6.208Hw. 36,37 The most often cited value for dry PA-6 is T g % 327 K. 38,39 Furthermore, T g depends on the residual stresses and annealing. 40 In the present case, T g was difficult to detect as the starting temperature for PVT measurements (30 C) was close to the transition.…”
Section: Solid State Region At T < T Mmentioning
confidence: 99%